Control of flower induction in tropical/subtropical fruit trees by phytohormones using the example of longan and mango - M. Hegele (2018)
For many fruit trees originating from subtropical climates, cool temperatures or significant dry periods became key triggers of flower induction (FI). Under real tropical conditions, however, these environmental influences are, if at all, only present to a much lower extent, which frequently leads to insufficient FI. In such situations, at least for mango (Magnifera indica) and longan (Dimocarpus longan), it has been possible to enforce FI by application of paclobutrazol (GA-biosynthesis inhibitor) and KClO3 respectively, even when sufficiently low temperatures were missing. In this way it has been possible to reduce the problem of alternate bearing and it has also enabled the production of profitable off-season fruit. Because of this behaviour, these two species became the ideal model plants for our investigations on the hormonal regulation of FI, supported by data from further experiments under greenhouse conditions. With the exception of girdling in combination with NPA in mango and KClO3 application in young longan trees, where initially a short increase in photosynthesis (Pn) occurred, all these inductive treatments finally resulted in a significant reduction of Pn. In all cases, depending on the plant species, a increase in auxin transport from the leaves occurring over varying lengths of time could be observed, which, contradicts the usual hypothesis that higher export rates from young leaves, normally inhibit FI. In KClO3 -induced longan as well as in cool temperature treated mango a clear increase of cytokinins (CKs) in terminal buds is noted as well as a drop in gibberellins. Although in the case of longan this drop lasts only a short time, it could still help to explain the FI promoting activity of paclobutrazol or the inhibiting effect of gibberellins. At the same time, the concentrations of auxin (IAA) in the buds were usually significantly reduced. Furthermore, the increase in CKs, the group of hormones which for a long time, in apple for example, has been suspected to promote FI, could also be detected in the bark and wood of the treated trees. The sequence of the observed hormonal changes could be decisive for the channelling of the bud meristem growth towards generative development, in which the auxin signal might have some kind of transmitter function.